Extração de compostos bioativos da casca e polpa de romã (Punica granatum) com solventes e misturas - Santos, Jhenifer Cristina Carvalho (2022)
The pomegranate is a fruit originally from the Middle East and Asia that has adapted very well to Brazil, having a promising cultivation. Pomegranate has therapeutic characteristics due to the presence of bioactive compounds, mainly in the skin and pulp, highlighting compounds such as tannins and polyphenols and pectin, a polysaccharide with gelling properties widely used in the industry. The study of pomegranate peel and pulp separately would be a way of analyzing in which part the compounds of interest are found in greater quantity. The objective of the present work was to study the effect of using a mixture of ethanol, water and acetone solvents and temperature in the extraction of bioactive compounds from the pomegranate peel and pulp and subsequent quantification of pectin in the residue. Peel and pulp were analyzed for proximate composition, mineral content, pectin, titratable acidity, tannin content, total phenolic content and antioxidant activity by DPPH. In the first step, solid-liquid extraction was carried out using the dry and ground raw material in a stirred bath with constant temperature and time. In this step, the effects of solvent mixtures and extraction temperature by central rotational composite design (DCCR) on the extract composition were evaluated, regarding the content of phenolics, tannins, antioxidant capacity by DPPH and titratable acidity. In the second stage, an acid extraction with 3.5% citric acid was carried out to obtain the pectin from the pomegranate peel and pulp from the residues of the first stage, identifying the influence of the conditions used in the previous extraction of bioactive compounds in the first stage, in the pectin yield and degree of esterification. When analyzing the results, we can see that the dry raw material has a concentration of phenolic compounds in the pomegranate peel of 112.41 mg of GAE/g of sample and for the pulp 207.3741 mg of GAE/g of sample, tannin content in the pomegranate peel 42.22 mg of catechin/g of sample and for the pulp 23.62 mg of catechin/g of sample, and when extracting pectin from the peel and dried pomegranate pulp we obtained 9.41% and 6.61%, respectively. Among the pure solvents, water was more efficient for the extraction of phenolic compounds, antioxidant activity and obtaining pectin from the residue for both samples, pomegranate peel and pulp. The solvent mixtures were better than the pure solvents for the extraction of phenolic compounds, tannins, antioxidant activity and pectin from the residue, and the optimal parameters found for pomegranate peel and pulp in relation to ethanol:acetone:temperature were 30.8 %; 0%; 51°C and 20%; 33.6%; 57.3°C, respectively.